Using ERA5–Land Reanalysis and Data from Weather Stations in the Mountainous Regions of Russia to Assess Changes in the Glacial Systems of Eastern Siberia and the Far East - T. B. Titkova; M. D. Ananicheva (Лëд и снег)
This work involving the study of changes in the glacier equilibrium line altitude (ELA) is a continuance of the glaciological parameters of mountain systems investigation. The article explores the possibility of using new generation climate archives (in this case, ERA5–Land) together with weather station data on temperature and precipitation, in order to assess the climate dependence of the glacial system ELA in hard-to-reach and insufficiently studied mountain regions of the Russia Asian part. The ERA5–Land reanalysis reproduces temperature (values, dynamics, and trends) quite well in mountain systems. The use of total precipitation is possible only for assessing their dynamics and trends. The relative error for temperature trend is below 20% in both positive and negative sides, and precipitation is less than 30% in the negative one. Positive temperature trends of different intensity are observed in all mountains of the Russia Asian part with a maximum in the mountain systems of the Arctic zone. Minimal temperature trends are distinctive for coastal mountain regions of temperate latitudes. Summer temperature trends are maximum in inland areas and minimum in coastal mountain areas. The increase in precipitation in such areas occurs mainly at the expense of the cold period. It was revealed there was an increase of the glacial systems ELA from 50 to 800 m in the mountain regions of the Asian North Russia within 1966–2021. The value of the ELA rise coincides with areas of high temperature trends and may not correspond to precipitation negative trends.